SODIUM CHLORIDE AND NITRITE CONTENTS IN CANNED MEAT IN PIECES FROM THE SERBIAN MARKET - Tasić, Tatjana (Food and Feed Research, 2020)
Canned meat in pieces (CM) is a group of meat products widely consumed by children and consumers with special diet regimes, due to the high protein and low fat content. In this study safety of these products from sodium chloride and nitrite contents point of view was examined in total of 19 meat samples produced by 14 most represented meat processors on Serbian market. The statement about high protein and low fat content in CM for products from the Serbian market was confirmed. Products made from chicken meat (“Pileća prsa”, protein 12.4 to 17.4 g/100g; fat 0.92 to 3.84 g/100g) had higher protein and lower fat content that products made from pork (“Pizza šunka”, protein 11.5 to 14.3 g/100g; fat 4.61 to 14.4 g/100g). In the group “Pileća prsa” 90.91% of samples had sodium chloride content lower than 1.5 g/100g, while in the group “Pizza šunka” 75% of samples had sodium chloride content lower than 1.5 g/100g. Residual nitrite content in product “Pileća prsa” ranged from 0.62 to 20.7 mg/kg and in product “Pizza šunka” this content ranged from 3.27 to 19.2 mg/kg. These results indicate that all analised samples were below the required limits of nitrite content. According to the results obtained in this study, children and consumers with special diet regimes are free to consume Serbian meat products in the type of CM from protein and fat, as well as from sodium chloride and nitrite content point of view.
Keywords: meat products; chicken; pork; protein content; fat content; safety